Differences in movement behaviour between successful and less successful goalkeepers in the interception of corner kicks - Abellán, J.; Saez-Gallego, N. M.; Vila-Maldonado, S.; Contreras, O. (Journal of Human Sport & Exercise, 2017)
The aim of this study is to analyze the movement behavior of young football goalkeepers when they try to catch balls from corner kicks. Goalkeepers were classified on their success during the interception, creating two groups of analysis, successful and less successful goalkeepers. The most successful goalkeepers obtained a higher success rate with a motor behavior characterized by moving your hands later and therefore catch the ball later that goalkeepers less successful. These results show that the specific requirements of catch a ball from a corner kick are similar to the requirements of catch balls in other sports. They are therefore less similar to the anticipation of future actions on projections of global equities football.